Fibrinogen and Vascular Smooth Muscle Cell Grafts Promote Healing of Experimental Aneurysms Treated by Embolization - Raymond, Jean; Desfaits, Anne Cécile; Roy, Daniel (Stroke (1970), 1999)
Background and Purpose —Residual necks and recurrences frequently occur after endovascular treatment of cerebral aneurysms. Addition of fibrinogen and vascular smooth muscle cells (VSMCs) to the embolic material may promote healing of embolized aneurysms by increasing neointima formation at the neck. Methods —Bilateral carotid aneurysms were constructed with venous pouches in 31 dogs. Aneurysms were packed intraoperatively with bare Gelfoam sponges, sponges treated with fibrinogen, or fibrinogen sponges seeded with the animal’s own VSMCs or peripheral blood mononuclear cells. Animals were killed after angiography at 3 weeks, and morphometric studies were performed to measure the thickness of the neointima at the neck of treated lesions. Angiographic results and mean thickness of neointimas were compared using ANOVA. In 8 animals, 1 aneurysm was embolized with sponge seeded with VSMCs transduced by adenoviral infection to express a fluorescent protein (green fluorescent protein), and gene expression was monitored for 4, 7, 14, and 21 days by fluorescent microscopy. Results —Aneurysms treated with sponges seeded with VSMCs had significantly thicker neointimas and were more completely obliterated at 3 weeks than control aneurysms treated with fibrinogen sponges. Peripheral blood mononuclear cells could not reproduce these findings. Sponges treated with fibrinogen alone promoted formation of a thicker neointima than bare sponges. Transduced cells transplanted into in vivo aneurysms still expressed green fluorescent protein at 3 weeks. Conclusions —VMSC grafts can improve healing of experimental aneurysms treated by embolization. Transplantation of cells transduced to express a foreign gene opens the way for in situ gene therapy for cerebral aneurysms.